1, 2, 3-Triazole lamellar liquid crystal and its non-covalent palladium complex dimer: structure, mesomorphism and self-assembly properties. Issue 1 (2nd January 2022) - Xia, Meihao; Chen, Yao; Chen, Ziran; Yu, Wenhao; Cheng, Haomin; Feng, Chun; Ni, Hailiang; Wang, Biqin; Zhao, Keqing; Hu, Ping
ABSTRACT: 1, 4-disubstituted 1H-1, 2, 3-triazoles L was successfully synthesised using a catalyst-free click reaction between an internal alkyne and an azide compound. Refluxing click product L and palladium chloride in a homogeneous mixed solvent led to the formation of the non-covalent palladium chloride complex PdCl2 -L2, which was characterised by X-ray crystallographic analysis of the template compound, indicating that the complex adopts predominant trans-trans isomeric orientations. The two compounds showed a typical fan-shaped texture of the lamellar mesophase. Because of weak Pd-N coordination bond connections, PdCl2 -L2 is a monotropic liquid crystal with a narrower mesomorphic temperature range and relatively poorer thermal stability than ligand L . Furthermore, both L and the complex dimer can self-assemble into strip-shaped nanostructures on the oriented graphite substrate surface. Graphical abstract: uf0001